The seaside homecoming [large type] - Klassen, Julie, 1964- (Klassen, Julie, 1964- On Devonshire shores, 2025)
"Claire Summers replies to an advertisement to help run a Sidmouth boarding house, but her handsome, secretive business partner might send her packing if he learns her genteel façade hides a less-than-respectable past. And will a hoped-for reunion with her family lead to reconciliation or leave her estranged forever?" --